2018
DOI: 10.1002/app.47361
|View full text |Cite
|
Sign up to set email alerts
|

Impact of shape (nanofiller vs. nanorod) of TiO2 nanoparticle on free‐standing solid polymeric separator for energy storage/conversion devices

Abstract: We report the investigation on examining the impact of nanofiller (NF)‐ versus nanorod (NR)‐shaped titanium oxide (TiO2) nanoparticle on the structural, electrochemical, transport, thermal, and dielectric properties of the solid polymer electrolyte (SPE). Thin SPE films comprising of poly(ethylene oxide), sodium hexafluorophosphate, and dispersed with TiO2 NF, TiO2 NR (synthesized by hydrothermal route) has been prepared via solution cast technique. The shape of nanoparticle influences the morphological and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 92 publications
1
12
0
Order By: Relevance
“…A survey of literature confirms that for the lithium-ion conducting SPE materials, the LiClO 4 is one of the appealing ionic dopants used enormously for the preparation of SPEs [10,23,27,33,36]. The investigations on numerous NSPE materials have claimed that the dispersion of TiO 2 nanoparticles mostly increases the ionic conductivity, and some studies also reported an unexpected increase by a few orders of magnitude [22,23,30,[49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Some studies have concluded that only the acidic groups surface-modified TiO 2 and some other inorganic nanofillers are effective in increasing the conductivity of the NSPE materials [63,64].…”
Section: Introductionmentioning
confidence: 88%
“…A survey of literature confirms that for the lithium-ion conducting SPE materials, the LiClO 4 is one of the appealing ionic dopants used enormously for the preparation of SPEs [10,23,27,33,36]. The investigations on numerous NSPE materials have claimed that the dispersion of TiO 2 nanoparticles mostly increases the ionic conductivity, and some studies also reported an unexpected increase by a few orders of magnitude [22,23,30,[49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Some studies have concluded that only the acidic groups surface-modified TiO 2 and some other inorganic nanofillers are effective in increasing the conductivity of the NSPE materials [63,64].…”
Section: Introductionmentioning
confidence: 88%
“…The crystallite size also known as coherent length is tabulated in Table 2 and we can observe that the values of τ are decreased upon inclusion the nanofillers in both systems. This indicates that the degree of crystallinity of two broad humps has decreased, implying an amorphous phase in the CGPE systems that provide more free volume for the transportation of ions via interaction of nanofiller‐polymer and ion‐polymer 39–41 . In addition, the crystallinity index of the CGPE can be calculated from the ratio of the integrated area of all crystalline peaks to the total integrated area under the XRD peaks using Equation () as follows: %Crystallinity=IcIc+Ia×100, where, I a and I c are the integrated intensities corresponding to the amorphous and crystalline phases obtained from the area under the curve of XRD graph using OriginPro, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Further, Arya et al. [ 111 ] comparatively studied the effect of different shapes of TiO 2 nanoparticles (nanofiller vs nanorod) on electrochemical properties of SPEs, and showed that the ionic conductivity was sensitive to the shape of nanoparticles, and the PE with the addition of TiO 2 nanorods presented superior properties (dielectric nature, electrochemical window, ionic conductivity) than that added with TiO 2 nanofillers.…”
Section: Pes For Na‐ion Batteriesmentioning
confidence: 99%